(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Indonesia has held its general election on April 17th, 2019. During the 2019 general election, there were 11.239 members of polling station KPPS members passing out and 527 people passing away. Due to this circumstance, forensic examination is required to examine the reason behind the cases of the dead and the sick members. Therefore, this present article analyzes two issues: 1) how legal effort is conducted regarding health services provided for polling station KPPSmembers; and 2) what action the government do to take the responsibility on the death of the members. This research is categorized as legal research that employs four approaches. The first approach is statuary approach by using ordinatie sth No. 350 of 1957 Visum Et Repertum, preamble of 1945 State Constitution of Republic Indonesia article 179 of Criminal Code, Law of Health No. 36 of 2009 and Election Law No. 7 of 2017. The second one is case approach. The next is conceptual approach for both death and ill health cases. The last one is using comparative approach. The result showed that the members of polling station committee died due to some illness suffered by the members such as cardiovascular, heart attack, stroke, or even all of them. However, for members who do not suffer from hereditary disease, the cause the death is due to the heavy workload they had that surpasses 20 until 22 hours a day. Besides, lack of sleep is also considered contribute to the members’ death and sickness.